A STUDY OF SIGNS: The Political Advertisements in Presidential Election Campaign of Indonesia 2014 based on the Peirce’s Theory - Henny Uswatun Hasanah (IAIN MADURA, 2014)
In general election especially presidential election, it will have a special thing like in using advertisements for doing a campaign. In 2014, Indonesia has two candidates for becoming the first position as president and vice president. It is interested in analyzing the signs of advertisements that becomes their personal branding using semiotics analysis. This paper focuses on Peirce’s theory that is related to the signs which are able to be defined as three categories; Icon, Index and Symbol. There are many signs in personal branding of each candidate such as Prabowo-Hatta has a nationalist enthusiasm for Indonesia. Then, Jokowi-JK has an eternal spirit for working. Of course, the analysis is interested in analyzing to know more the meaning of signs because it is able to be an effective to use in campaign for getting many voters in a polling day. Therefore, as society has to be critical in this thing for choosing the right man as president and vice president of Indonesia.